1996
DOI: 10.1002/etc.5620150925
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced accumulation of PCB congeners by baltic sea blue mussels, Mytilus edulis, with increased algae enrichment

Abstract: Abstract-The objective of this study was to examine if natural variations in the quantity of phytoplankton-derived particulate and dissolved organic carbon influences the accumulation of polychlorinated biphenyls (PCBs) in the tissues of Baltic Sea blue mussels (Mytilus edulis L.). In a laboratory flow-through experiment we exposed M. edulis to the technical PCB mixture Aroclor 1248 for 21 d at three different enrichments of the unicellular green algae Chlamydomonas sp., 0.10, 0.16, and 0.32 mg particulate org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 39 publications
0
2
1
Order By: Relevance
“…Contrary to what could be expected, given the results from earlier experimental studies (Gilek et al 1996; Björk and Gilek 1997; Gunnarsson et al 2000), we found that PCB concentrations in profundal benthos (chironomid larvae) were negatively related to lake trophic status. In earlier experiments, marine filter-feeding mussels were exposed to additions of algae at different concentrations.…”
Section: Lake Trophycontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to what could be expected, given the results from earlier experimental studies (Gilek et al 1996; Björk and Gilek 1997; Gunnarsson et al 2000), we found that PCB concentrations in profundal benthos (chironomid larvae) were negatively related to lake trophic status. In earlier experiments, marine filter-feeding mussels were exposed to additions of algae at different concentrations.…”
Section: Lake Trophycontrasting
confidence: 99%
“…Gunnarsson et al (2000) found in laboratory experiments that POP concentrations in benthic animals could, contrary to pelagic biota, increase with increasing trophic status of water bodies. Owing to increasing settling of organic-rich particles, the benthic bioactivity increases with increasing disturbance of the sediment (bioturbidation) (Gilek et al 1996;Björk and Gilek 1997;Madsen et al 1997). Bioturbation and increasing ventilation rates of sediments could enhance bioaccumulation of POPs in benthic invertebrates (Swackhamer and Skoglund 1993;Madsen et al 1997;Gunnarsson et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Bioaccumulation of hydrophobic organic pollutants and eutrophication are two serious threats to the marine environment. Since eutrophication leads to an increased production of organic matter and hydrophobic organic compounds (HOCs) have a high affinity for organic surfaces, there is a growing interest in how the two phenomena interact [1,2].…”
Section: Introductionmentioning
confidence: 99%